PERANCANGAN MEDIA PROMOSI PT. SAHABAT MEDIKA SEJAHTERA SEBAGAI UPAYA MEMPERTAHANKAN BRAND LOYALTY - Andrele, Jessy Octavia; Bahruddin, Muh; Aliffianto, Achmad Yanu (Jurnal Art Nouveau, 2014)
Brand is an important part of all cultures around the planet and also in the business world. A company must be understand that branding is not just building a name, but it comes to keeping promises, that offers given by companies will create and provide a certain level of performance. Brand promise become the motive force of all activities of the company and its partners. PT. Sahabat Medika Sejahtera is environmental medical distributor based in Sidoarjo. However, due to the lack of knowledge about branding is less, resulting in sales of PT. Sahabat Medika Sejahtera prosperity is not increased. Therefore, it required an appropriate promotional media provide knowledge to partners and customers so that they will understand the vision and mission of the company. This brings the concept of media promotion business to business which aims to make the company have an effective promotion as well as right on target.